Test on interior precast concrete beam-to-column connection with tension lap method - Ahmad Baharuddin Abd. Rahman, author; Abdul Rahim Ghazali, author; Zuhairi Abd. Hamid, author; National Seminar on Civil Engineering Research (2007 : Johor) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL